Combined effects of chemical fertilization and microbial inoculant on nutrient use efficiency and soil quality indicators - Angulo, Jimena (2020)
Microbial inoculant based on beneficial bacteria is a complementary management tool to increase vegetable production. However, its integration with chemical fertilization has been poorly studied. The present study evaluated the effects of microbial inoculant separately and in combination with chemical fertilization on lettuce under greenhouse conditions. An experiment was performed in pots using a completely randomized design. The microbial inoculant was applied at three fertilization levels. Soil response evaluated variables were: available N and P, total soil bacteria, soil enzymatic activities, and N leaching. Agronomic variables measured were: aerial biomass, chlorophyll content, and nutrient foliar contents. Microbial inoculant had a significant impact on soil total bacteria concentration. The application of reduced chemical fertilization and microbial inoculant had a similar effect in terms of soil nutrient availability and soil enzymatic activities as the complete fertilization. Nitrogen leaching was strongly dependent on chemical fertilization rate. Treatment application decreased chlorophyll concentration compared to the control. The application of microbial inoculant and chemical fertilization increased foliar N and P contents improving their uptake. The combined addition of microbial inoculant with chemical fertilization increases the bacteria concentration without altering enzymatic activities, maintaining similar soil nutrient levels and improving N and P uptake in lettuce. Future studies could be performed in lettuce to determine the impact under different growth stages and different soil conditions.